Cosmetic application behaviours and their association with sensitive skin in young adult women - Saraswati, Ni Wayan Citra Ayu; Sari, Dian Puspita; Hidajat, Dedianto (Faculty of Medicine, Universitas Islam Indonesia, 2026)
Background: Sensitive skin is an uncomfortable sensation on the skin that arises due to a response to stimuli that normally do not cause discomfort. Women more commonly experience it than men. Recent evidence indicates that cosmetic use is the predominant triggering factor compared to other factors, particularly in women, due to the extensive and varied use of products. Objective: This study examined the relationship between the number of cosmetic products used daily and weekly and the incidence of sensitive skin among young adult females.Methods: This cross-sectional study employed a stratified random sampling method. The study population involved young female adults who agreed to participate after completing the informed consent form. The exclusion criteria were facial inflammation and use of oral or topical medication containing corticosteroids. The cosmetic usage pattern was assessed through a questionnaire. Skin sensitivity assessment was conducted by utilizing the lactic acid stinging test (LAST), where 10% aqueous lactic acid solution was topically applied to the right nasolabial fold region. The mann-whitney test was employed to analyze the relationship between the number of cosmetic products used daily and weekly and the occurrence of sensitive skin. Results: Out of 136 subjects, 23.5% have sensitive skin based on the LAST. The most prevalent products used by the majority of respondents are facial wash, sunscreen, and moisturizer, with a percentage of >70%. No significant relationship is found between the number of products used daily and weekly and sensitive skin (p > 0.05). Conclusion: No significant differences regarding the number of products used among sensitive and non-sensitive skin groups. Therefore, future studies are needed to explore the ingredients in cosmetic products and their volume of usage, as well as to conduct prospective studies assessing the impact of cosmetic usage patterns on the occurrence of sensitive skin.